2022
DOI: 10.1186/s12887-022-03360-9
|View full text |Cite
|
Sign up to set email alerts
|

Screening and management of bladder and bowel dysfunction in general pediatric outpatient clinic: a prospective observational study

Abstract: Background Bladder and bowel dysfunction (BBD) is a common disorder in children that is often associated with psychosocial and behavioral problems. Data specific to BBD in Asian children are comparatively scarce. Accordingly, this study aimed to investigate the prevalence of BBD and the response to standard urotherapy among Thai children attending the general pediatric outpatient clinic of Siriraj Hospital – Thailand’s largest national tertiary referral center.  M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The authors also showed that a score of 11 had diagnostic sensitivity and specificity of 80% and 91%, respectively. The high sensitivity and specificity of the VSS questionnaire indicate that this instrument is a valuable screening tool, since it allows the early identification and referral of children and adolescents with symptoms of BBD to specialized centers ( 3 , 5 , 7 , 9 11 ). The early diagnosis and adequate multidisciplinary treatment can avoid the repercussions for the upper urinary tract mainly represented by renal scars ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also showed that a score of 11 had diagnostic sensitivity and specificity of 80% and 91%, respectively. The high sensitivity and specificity of the VSS questionnaire indicate that this instrument is a valuable screening tool, since it allows the early identification and referral of children and adolescents with symptoms of BBD to specialized centers ( 3 , 5 , 7 , 9 11 ). The early diagnosis and adequate multidisciplinary treatment can avoid the repercussions for the upper urinary tract mainly represented by renal scars ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early recognition and non-invasive management of BBD in children and adolescents in a general outpatient setting plays an important role in reducing morbidity ( 5 , 7 ). Several validated voiding scales are useful for this purpose ( 3 , 5 ), including the Dysfunctional Voiding Symptom Score (DVSS) ( 8 ) and the Vancouver Symptom Score (VSS) ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, similar to what has been reported in the literature, BBD was more commonly observed in girls. [2] Diagnosis of BBD is typically based on the patient's anamnesis and physical examination. [8] Most children do not require any diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
“…LUTS can present with symptoms such as incontinence, frequent urination, sudden need to urinate, di culty initiating urination, straining to urinate, weak urine ow, intermittent urination, and dysuria. [2] Thus, complications such as urinary tract infections, vesicoureteral re ux (VUR), and/or renal function loss may occur. [2] An early diagnosis and treatment of constipation in these patients can help prevent complications by preventing chronic progression of LUTS symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation